Forest Landscape Restoration in the Drylands of Latin America - Newton, Adrian C. (2012)
Forest Landscape Restoration (FLR) involves the ecological restoration of degraded forest landscapes, with the aim of benefiting both biodiversity and human well-being. We first identify four fundamental principles of FLR, based on previous definitions. We then critically evaluate the application of these principles in practice, based on the experience gained during an international, collaborative research project conducted in six dry forest landscapes of Latin America. Research highlighted the potential for FLR; tree species of high socioeconomic value were identified in all study areas, and strong dependence of local communities on forest resources was widely encountered, particularly for fuelwood. We demonstrated that FLR can be achieved through both passive and active restoration approaches, and can be cost-effective if the increased provision of ecosystem services is taken into account. These results therefore highlight the potential for FLR, and the positive contribution that it could make to sustainable development. However, we also encountered a number of challenges to FLR implementation, including the difficulty of achieving strong engagement in FLR activities among local stakeholders, lack of capacity for community-led initiatives, and the lack of an appropriate institutional and regulatory environment to support restoration activities. Successful implementation of FLR will require new collaborative alliances among stakeholders, empowerment and capacity building of local communities to enable them to fully engage with restoration activities, and an enabling public policy context to enable local people to be active participants in the decision making process.